2020
DOI: 10.1111/papq.12302
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Implicit Bias: Putting the Criticism into Perspective

Abstract: What is the status of research on implicit bias? In light of meta‐analyses revealing ostensibly low average correlations between implicit measures and behavior, as well as various other psychometric concerns, criticism has become ubiquitous. We argue that while there are significant challenges and ample room for improvement, research on the causes, psychological properties, and behavioral effects of implicit bias continues to deserve a role in the sciences of the mind as well as in efforts to understand, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 115 publications
(205 reference statements)
3
66
2
Order By: Relevance
“…For example, expanding on the predictions derived from dual‐process theories, implicit and explicit measures have been used to predict different kinds of behavior (e.g., spontaneous vs. deliberate behavior), the same behavior under different conditions (e.g., under cognitive load), and the behavior of people with varying personality traits (e.g., intuitive vs. deliberative thinking style). (See Brownstein et al, ; Friese, Hofmann, & Schmitt, , for extensive discussions of evidence for these predictions.) As we discuss below, these behavior‐, context‐, and person‐related variables should and do moderate the relations between implicit measures and other kinds of behavior (e.g., evaluating CVs).…”
Section: Associative And/or Propositional Representationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, expanding on the predictions derived from dual‐process theories, implicit and explicit measures have been used to predict different kinds of behavior (e.g., spontaneous vs. deliberate behavior), the same behavior under different conditions (e.g., under cognitive load), and the behavior of people with varying personality traits (e.g., intuitive vs. deliberative thinking style). (See Brownstein et al, ; Friese, Hofmann, & Schmitt, , for extensive discussions of evidence for these predictions.) As we discuss below, these behavior‐, context‐, and person‐related variables should and do moderate the relations between implicit measures and other kinds of behavior (e.g., evaluating CVs).…”
Section: Associative And/or Propositional Representationsmentioning
confidence: 99%
“…We are more sympathetic to some of these criticisms than others. Elsewhere we have addressed specific lines of criticism in detail (Brownstein, in press; Brownstein, Madva, & Gawronski, ; Gawronski, in press; Madva, , ). Here we step back from any one set of concerns in order to try to reframe the discussion a bit.…”
Section: Introductionmentioning
confidence: 99%
“…Although this study has several strengths, such as eliciting children's sympathy and personal distress through videos with realistic scenarios and focusing on young White children's biased feelings of sorrow and nervousness toward their own racial group and its relation to parents' implicit race attitudes, the limitations of the current study, which imply future research needs, should also be recognized. First, future studies should include parents' explicit and implicit attitudes (rather than only implicit ones) in predicting children's behaviors (Brownstein et al, 2020). Second, researchers should use longitudinal data to capture the development and direction of effects in understanding the socialization of White children's sympathetic bias favoring White victims (Baron, 2015;Payne, Vuletich, & Lundberg, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Implicit racial attitudes are those beliefs and values that can be spontaneously triggered by mere presence of attitude stimuli and direct behaviors without participants' full awareness and control (Greenwald & Banaji, 1995). Both implicit and explicit race attitudes make distinctive contributions in predicting individuals' behaviors (Brownstein, Madva, & Gawronski, 2020), but studies have shown that implicit race attitudes uniquely predict people's nonverbal behaviors when interacting with outgroups above and beyond explicit race attitudes (Jost, 2019;Kurdi et al, 2019;McConnell & Leibold, 2001).…”
Section: Parents' Implicit Racial Attitudesmentioning
confidence: 99%
“…For example, Oswald and colleagues (), have claimed on the basis of their meta‐analysis of IAT results, that it is a “poor” predictor of subsequent behaviour. I note a handful of things in response (see IAT roundtable on the Brains Blog, and Brownstein, Madva, & Gawronski, manuscript, for discussion). First, in comparing Oswald and colleagues' meta‐analysis to their own earlier one (2009), Greenwald and colleagues argue that the differences between the two are due to a difference in method.…”
mentioning
confidence: 99%